PEMODELAN PEMILIHAN MODA ANTARA MONOREL TERHADAP BUSWAY DENGAN METODE STATED PREFERENCE - Tommy Bahtiar Saputra; Amirotul MHM; Setiono Setiono (Matriks Teknik Sipil, 2013)
The monorail is part of the main strategy macro transportation pattern in the Jakarta, one of the routes that will be developedis cawang -east bekasi. This study aims to find the modal choice behavior modeling monorail on busway mode usingstated preference methods. In the study, the influence of the attributes used in the form of fare determination, reduction oftravel time, and waiting time. The data used in this study is the secondary data obtained from pollsters a passenger responseto the stated preference method is by providing eight different scenarios.Modelling is done by using a binomial logit models. The selection of model is obtained as follows:Umr -bwy = -5,6356 - 0,0007339(Fmrl - Fbwy) + 0,4316(TRedctnmrl -TRedctnbwy)with F is a variable fare , TRedctn is the variable reduction of travel time. Based on the obtained model, variable reductionof travel time becomes the biggest aspect in the selection mode .